THE ROLE OF PHONETICS IN TEACHING ORAL ENGLISH AT THE UNIVERSITY - Kobylianska, I. V. (НАУКОВІ ЗАПИСКИ, 2019)
This article analyzes the role and importance of the development of pronunciation skills in teaching oral English at the university. Apart of given a description of the different characteristic or peculiarities of the English sound system, the numerous activities at all levels which can be used to develop and practice pronunciation skills in the EFL classroom have been reviewed. Sounds are classified firstly into whether they are consonants or vowels. However, the sounds of English not make up the whole picture of pronunciation because “speech is a continuum without clear cut borderlines between individual sounds”. It has been determined that there are six principal functions of intonation: emotional, grammatical, informational, textual, psychological, indexical. All speech events could be described according to a series of factors when the speakers engage in conversation: prominence, topic management, information status, turn-taking, social meaning and roles, degree of involvement. Finally, it have been explored that there are numerous possibilities which can be used for students to develop and practies their pronunciation skills in the classroom ranging from the most simple question and answer exercises, through meaningful drills of new strucrures, prepared dialoges or substitution exercises, and others. The great majority of exercises in textbooks can be carried out equally efficiently as oral exercises.